Pengaruh Kualitas Produk dan Promosi Produk terhadap Keputusan Pembelian Fashion Lokal dan Produk Impor Thrifting di sekitaran Kota Bandung - Dzaky Naufal Zhafran; Halimah Zahrah; Indra Sasangka (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
As one of the major fashion industry centers in Indonesia, Bandung has experienced significant growth in both local fashion brands and the imported thrifting market, creating an interesting competitive landscape in consumer preferences. This research employs a quantitative approach using descriptive and verificative methods. Data were collected through questionnaires distributed to 30 respondents aged 20–35 years who reside in Bandung City and have purchased local fashion or imported thrifting products within the last six months. The data were measured using a five-point Likert scale and analyzed through validity and reliability tests as well as statistical analysis to examine the partial and simultaneous effects of the variables. The results indicate that product quality and product promotion have a positive influence on consumer purchase decisions for both local fashion and imported thrifting products. Product quality plays a crucial role in building consumer trust, while promotion contributes to increasing purchase interest and encouraging buying actions. Simultaneously, product quality and product promotion have a significant effect on purchase decisions. This study is expected to serve as a reference for local fashion businesses and thrifting sellers in developing more effective quality improvement and promotional strategies.